PERAN BIMBINGAN KONSELING ISLAM DALAM MEMINIMALISIR PENGGUNAAN BAHASA NON ETIS PADA SISWA KELAS IX DI MTS NURUL AEYN AS’ADIYAH KAMPUNG BARU KECAMATAN TELLU SIATTINGE KABUPATEN BONE (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2025)
This study examines the Role of Islamic Guidance and Counseling in Minimizing the Use of Non-Ethical Language among Ninth Grade Students at MTs Nurul Aeyn As’adiyah Kampung Baru, Tellu Siattinge District, Bone Regency. The research focuses on two main questions: (1) How do Islamic Guidance and Counseling teachers minimize the use of non-ethical language among ninth-grade students at MTs Nurul Aeyn As’adiyah Kampung Baru? (2) What are the outcomes of the efforts made by the counseling teachers in reducing non-ethical language among these students? This research employs a qualitative descriptive method using an Islamic counseling approach. The primary data source is Bahri as the key informant, supported by additional informants including Makmur, Husnah, Binti, and A. Asdar, along with three students: Muh. Norman, Syakilah, and Jumasna. Secondary data were obtained from books, journals, articles, and other references. Data were collected through observation, interviews, and documentation, with the researcher serving as the main instrument. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings indicate that Islamic Guidance and Counseling plays a significant role in reducing students’ use of non-ethical language. (1) The strategies implemented by the counseling teacher include giving warnings, conducting mediation and personal approaches, providing individual and group counseling, administering educational sanctions, and collaborating with parents. (2) These efforts resulted in positive outcomes such as increased student awareness of their mistakes, reduced frequency of inappropriate language, enhanced understanding of ethical communication, decreased potential conflict, and the development of akhlaqul karimah among students. The implications of this study suggest that: (1) Islamic Guidance and Counseling teachers should continue to strengthen their skills in applying effective Islamic counseling methods, emphasizing personal approaches and collaboration with parents to nurture students’ ethical communication. (2) Students are expected to become more aware of the negative impacts of harsh language and develop better self-control to create a harmonious school environment.